The Impact on Public Health and Economy Using Lockdown as a Tool against COVID-19 Pandemic in Africa: A Perspective - Nyarko, Richard Owusu; Boateng, Edward; Kahwa, Ivan; Boateng, Paul Owusu; Nyarko, Rosemond Owusu; Asare, Bertram; Asum, Christian; Ampong, Grace Ama; Nayembil, Daniel Azumah (Journal of Epidemiology and Public Health Reviews, 2020)
Background: Since the spread of Corona Virus Disease 19 (COVID-19) most African countries have embarked on a system of either total or partial lockdown and have used it as a tool for curbing the spread of COVID-19. This study examines whether lockdown can be of help and whether it is any of the public health policies that can bring massive and tremendous change to health systems and general economy of African countries using it as a way of intervention to curb the spread of COVID-19. Method: The researchers reviewed some literature about world economies with Google as the main search tool. They also listened to press conferences, editorial reviews from the African Union, World Bank, International Monetary Fund, and the World Health Organization. Interviews were also done through phone calls, questions asked via emails to some of the world’s leading epidemiologists, infectious disease specialists in the United States of America, Europe, Africa, and some of the listed countries in their work. Results: After a careful study and analysis of countries like Hong Kong, South Korea, Japan, Singapore, Taiwan who did not really make lock down as a major measure in fighting the COVID-19 disease still saw a stable economy, a drastic containment of the pandemic, few deaths and more recoveries as compared to countries in Africa like south Africa which is the worst affected African country, Nigeria, Morocco, Egypt, Kenya, Ghana, Uganda, the Gambia, Sierra Leone, Senegal that embarked on massive lockdown either partially or completely but still showing plummeting inflation, declining gross domestic product, loss of capital for business groups, loss of jobs especially in the informal sectors, (negative growth with Ghana an exception) due to disruption of the world economy through global value chains, abrupt fall in commodity prices and fiscal revenues and enforcement of travel and social restrictions all due to the COVID-19 pandemic. The researchers found that a total lockdown without Mass testing which is best or symptomatic testing for countries with fallen and weak economies since mass texting is capital intensive, Contact Tracing and Treating that are strongly interspersed with Public and Community health education and health campaigns through the mass media in both international and local dialects, all efforts of lock down become a zero or empty and defective process and this shows that lock down is no cure, has never been a cure, and shall not be a cure to the COVID-19 pandemic and any other future pandemics. Conclusion: The researchers think that it is time public health systems of African countries are strengthened with befitting budgets, human resource developments of all kinds of cadres in the health and economic sectors, more public health educators should be recruited to use the mass media be it local radio stations, television stations, internet to educate the masses in their local dialects for better understanding on the effects of COVID-19 pandemics on respective countries, precautions, preventions and safety steps to follow even when one is suspected to have been infected with the disease. It is now time for African countries to adapt tailored measures in fighting the COVID-19 pandemic putting into consideration their culture diversity, local economies, climatic conditions, availability of resources and funds and only use the World Health Organization’s guidelines as a bench mark while African economies try to emulate from the pacesetter countries like Japan, South Korea, Hong Kong, Taiwan that have been able to contain the spread of COVID-19.
Keywords: COVID-19; Pandemic; Lock down; M3T; 2SQ; Economy